Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(P=\left(5x-1-5x-4\right)^2=\left(-3\right)^2=9\)
b: \(Q=\left(x+y\right)^3-3xy\left(x+y\right)=x^3+y^3\)
c: \(=\dfrac{\left(5^2-1\right)\left(5^2+1\right)\left(5^4+1\right)\left(5^8+1\right)\left(5^{16}+1\right)}{2}\)
\(=\dfrac{\left(5^4-1\right)\left(5^4+1\right)\left(5^8+1\right)\left(5^{16}+1\right)}{2}\)
\(=\dfrac{\left(5^8-1\right)\left(5^8+1\right)\left(5^{16}+1\right)}{2}\)
\(=\dfrac{5^{32}-1}{2}\)
\(P=x^2+8x+16+x^2-25-2x^2-2x=6x-9\\ Q=y\left(x-4\right)-5\left(x-4\right)=\left(y-5\right)\left(x-4\right)\\ Q=\left(5,5-5\right)\left(14-4\right)=0,5\cdot10=5\)
a) Ta có: \(B=\dfrac{x^2}{5x+25}+\dfrac{2\left(x+5\right)}{x}+\dfrac{50+5x}{x\left(x+5\right)}\)
\(=\dfrac{x^2}{5\left(x+5\right)}+\dfrac{2\left(x+5\right)}{x}+\dfrac{50+5x}{x\left(x+5\right)}\)
\(=\dfrac{x^3}{5x\left(x+5\right)}+\dfrac{10\left(x+5\right)^2}{5x\left(x+5\right)}+\dfrac{250+25x}{5x\left(x+5\right)}\)
\(=\dfrac{x^3+10x^2+100x+250+250+25x}{5x\left(x+5\right)}\)
\(=\dfrac{x^3+10x^2+125x+500}{5x\left(x+5\right)}\)
\(=\dfrac{x^3+5x^2+5x^2+25x+100x+500}{5x\left(x+5\right)}\)
\(=\dfrac{x^2\left(x+5\right)+5x\left(x+5\right)+100\left(x+5\right)}{5x\left(x+5\right)}\)
\(=\dfrac{\left(x+5\right)\left(x^2+5x+100\right)}{5x\left(x+5\right)}\)
\(=\dfrac{x^2+5x+100}{5x}\)
b) Thay x=-2 vào biểu thức \(B=\dfrac{x^2+5x+100}{5x}\), ta được:
\(B=\dfrac{\left(-2\right)^2+5\cdot\left(-2\right)+100}{-5\cdot2}=\dfrac{4+100-10}{-10}=\dfrac{94}{-10}=-\dfrac{94}{10}=\dfrac{-47}{5}\)
Vậy: Khi x=-2 thì \(B=-\dfrac{47}{5}\)
a) ( x + 3 )( 1 - x ) + ( 2x + 1 )2
= x - x2 + 3 - 3x + 4x2 + 4x + 1
= 3x2 + 2x + 4
b) ( x - 5 ) + x( x2 + 5x + 1 ) - ( x - 1 )3
= x - 5 + x3 + 5x2 + x - ( x3 - 3x2 + 3x - 1 )
= x3 + 5x2 + 2x - 5 - x3 + 3x2 - 3x + 1
= 8x2 - x - 4
P=(5-x)(x+5)+(x-3)^2+5x
=25-x^2+x^2-6x+9+5x
=-x+34